MOTHER TONGUE-BASED MULTILINGUAL EDUCATION (MTB-MLE) IN THE PHILIPPINES: ITS IMPLICATIONS TO LANGUAGE LEARNING - Aldrin Laruan Apolonio (Universitas Brawijaya, 2022)
This research studied the influences of the mother tongue-based multilingual education (MTB-MLE) program in the Philippines in the learning of the English language. The research utilized the case study method to make a thorough, dimensional consideration of MTB-MLE in the Philippines. The research detailed the history of the case and focused on the key issue of the effects of the mother tongue in learning. The study found that there is a need to re-evaluate the MTB-MLE in the Philippines since many language acquisition theories stress the learning of English at an early stage and the teaching of English is not the exclusive concern of the English teacher. Likewise, English is needed by the learner since many written and online data are practically recorded in English and the majority of the social media programs are aired in the English language. The study recommends that the MTB-MLE should be re-evaluated by the Philippine Department of Education (DepEd) and that the mother tongue should be used merely as an auxiliary (supplementary or supporting) language in teaching.